The catching up of the Hungarian economy in the European Union and Hungary’s falling behind among the post socialist member states - Gábor Gulácsi; Ádám Kerényi (Journal of Government and Economics)
For decades Hungary, like the other post-socialist Central-Eastern European countries, followed a general policy of establishing and strengthening the institutions of democracy and a market economy. While Hungary initially benefited from the EU's convergence mechanisms, including access to the single market and cohesion funds, its long-term catching-up performance has lagged behind its regional peers. However, since the elections of 2010, when Viktor Orbán returned to power, Hungary has done dramatic changes. This study examines the complex interplay of factors that have shaped Hungary’s economic trajectory within the EU, focusing on two distinct periods: before 2010 and 2010–2023. Through international comparative analysis and country-specific hypotheses, the paper identifies critical governance failures and institutional weaknesses as primary reasons for Hungary's faltering convergence. In the early stages of Hungarian EU membership, the country’s economic development was hampered by a serious failure of governance of social-liberal parties which also triggered an excessive deficit procedure. After 2010 the functioning of the new illiberal government caused the country to lose ground in the economic catching-up process within the European Union. This setback has manifested through two institutional and two resource allocation-related symptoms, which can be traced back to a more fundamental explanation: the core institutional architecture and political objectives underpinning the Orbán model. Our findings underscore the ongoing tensions between Hungary’s domestic political agenda and the principles underpinning EU integration, raising concerns about Hungarian EU membership.